THE IMPACT OF DIGITAL EDUCATION TOWARDS A SUSTAINABLE DIGITAL CONSUMER IN THE ERA OF CIRCULAR ECONOMY - SONIA BUDZ; IOANA BUCUR-TEODORESCU; BOGDAN CRISTIAN ONETE (Journal of Engineering Studies and Research)
A more sustainable economy and society presume more sustainable behavior in terms of consumption. A change in this behavior could be brought by a change in demand. In other words, a change in the demand could be facilitated by one’s financial and digital education. The circular economy implies the reuse and recycling of products and materials over and over again; thus, the life cycle of products and materials is extended. Engaging in recycling should have future benefits. Recycling behavior and sustainability are interrelated, the recycling process is viewed as a key issue in sustainability and prevails as pro-environmental consumer behavior. It is already known that significant changes in individual behavior are essential for society to move toward sustainability. This paper aims to explore from a quantitative perspective if digital education has an impact on consumer behavior in terms of sustainability in the era of the circular economy. This research is useful for all providers, consumers, and stakeholders involved in different businesses